2009
DOI: 10.1093/annhyg/mep044
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Wood Dust Inhalation Exposure in the UK, 1985–2005

Abstract: Objectives: Wood dust data held in the Health and Safety Executive (HSE) National Exposure DataBase (NEDB) were reviewed to investigate the long-term changes in inhalation exposure from 1985 to 2005. In addition, follow-up sampling measurements were obtained from selected companies where exposure measurements had been collected prior to 1994, thereby providing a follow-up period of at least 10 years, to determine whether changes in exposure levels had occurred, with key staff being interviewed to identify fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…The average wood dust exposure levels in the present study were consistent with the previously reported studies, despite the fact that the sampling methods and sites were different in each study and the wood dust concentrations were not always TWA measurements (Moore et al , 1990; Hamill et al , 1991; Pisaniello et al , 1991; Scheeper et al , 1995; Martin and Zalk, 1998; Teschke et al , 1999; Schlünssen et al , 2001; Rando et al , 2005; Scarselli et al , 2007; Kalliny et al , 2008; Galea et al , 2009; Saejiw et al , 2009; Yamanaka et al , 2009; Kauffer et al , 2010). Wood dust exposure levels may have decreased over recent decades possibly due to the changes in equipment, production methods, and upgrading engineering ventilation system for dust control (Teschke et al , 1999; Galea et al , 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The average wood dust exposure levels in the present study were consistent with the previously reported studies, despite the fact that the sampling methods and sites were different in each study and the wood dust concentrations were not always TWA measurements (Moore et al , 1990; Hamill et al , 1991; Pisaniello et al , 1991; Scheeper et al , 1995; Martin and Zalk, 1998; Teschke et al , 1999; Schlünssen et al , 2001; Rando et al , 2005; Scarselli et al , 2007; Kalliny et al , 2008; Galea et al , 2009; Saejiw et al , 2009; Yamanaka et al , 2009; Kauffer et al , 2010). Wood dust exposure levels may have decreased over recent decades possibly due to the changes in equipment, production methods, and upgrading engineering ventilation system for dust control (Teschke et al , 1999; Galea et al , 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Wood dust exposure levels may have decreased over recent decades possibly due to the changes in equipment, production methods, and upgrading engineering ventilation system for dust control (Teschke et al , 1999; Galea et al , 2009). …”
Section: Discussionmentioning
confidence: 99%
“…This estimate is close to the mean wood dust concentrations (GM 2.8 mg m −3 , GSD 2.5) observed in our study, thus exposures have not declined significantly the last decade, and we can therefore not expect the SNC rates to decline. Other authors (Lee et al, 2011) suggest that wood dust exposure levels may have decreased over recent decades possibly due to the changes in equipment, production methods, and upgrading engineering ventilation systems for dust control (Teschke et al, 1999; Galea et al, 2009). Albeit the overall wood dust concentrations were similar to older studies, we do find some support for decreased wood dust concentrations in modern factories with improved occupational hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is significant information available regarding occupational exposure to wood dust and noise in peer-reviewed published literature from other parts of Canada [27] and internationally [812], there is almost no peer-reviewed published exposure data available which is from sawmills and veneer/plywood plants of Ontario.…”
Section: Introductionmentioning
confidence: 99%